Media multitasking, mind-wandering, and distractibility: A large-scale study - Wiradhany, Wisnu (Atten Percept Psychophys, 2019)
Previous studies suggest that frequent media multitasking – the simultaneous use of different media at the same time – may be associated with increased susceptibility to internal and external sources of distraction. At the same time, other studies found no evidence for such associations. In the current study, we report the results of a large-scale study (N=261) in which we measured media multitasking with a short media-use questionnaire and measured distraction with a change-detection task that included different numbers of distractors. To determine whether internally generated distraction affected performance, we deployed experience-sampling probes during the change-detection task. The results showed that participants with higher media multitasking scores did not perform worse as distractor set size increased, they did not perform worse in general, and their responses on the experience-sampling probes made clear that they also did not experience more lapses of attention during the task. Critically, these results were robust across different methods of analysis (i.e., Linear Mixed Modeling, Bayes factors, and extreme-groups comparison). At the same time, our use of the short version of the media-use questionnaire might limit the generalizability of our findings. In light of our results, we suggest that future studies should ensure an adequate level of statistical power and implement a more precise measure for media multitasking. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.3758/s13414-019-01842-0) contains supplementary material, which is available to authorized users.